Bilateral Killian-Jamieson Diverticula: A Case Report and Literature Review - René D Boisvert; Drew CG Bethune; David Acton; Denis R Klassen (Canadian Journal of Gastroenterology)
A Killian-Jamieson diverticulum is an outpouching from the lateral wall of the proximal cervical esophagus. These diverticula are rare and are distinct from the more commonly known Zenker’s diverticulum. Literature regarding Killian-Jamieson diverticula and its suggested management is scarce. The present report describes a patient with symptomatic bilateral Killian-Jamieson diverticula. The patient had both diverticula excised and an esophagomyotomy performed. Following surgery, the patient’s symptoms resolved and he recovered well. A literature review and discussion of the etiology, clinical presentation and radiographic findings of Killian-Jamieson diverticulum follow, as do recommendations for clinical management.